Brs biochemistry and molecular biology, fourth edition - D, Todd A. Swanson M.D. Ph.; PhD, Sandra I. Kim MD; PhD, Marc J. Glucksman ([S.l.] : Lippincott Williams & Wilkins, 2007)
BRS Biochemistry and Molecular Biology, Fourth Edition is an updated revision of a bestselling review, with an increased clinical focus, expanded molecular biology material, and several completely new chapters. The book outlines the important facts and concepts tested on the USMLE, within the context of physiologic functioning of the human body. Each chapter begins with a summary and ends with a high-yield summary to consolidate the material, so students can cover topics in a shorter time. Clinical vignette USMLE-style review questions, answers, and explanations appear after each chapter and in a comprehensive end-of-book exam. All the question material is also available online for electronic practice.
Keywords: biochemistry,molecular biology